Acting in Nigerian Video Films: A Critique of Lancelot Oduwa Imasuen’s Invasion 1897 - Jacob Shimrumun Ioraa (CV. Rayyan Dwi Bharata, 2022)
Acting plays a crucial function in the art of motion pictures. The art advance from making the audience participate in the director’s fantasy and take it as actuality. Actors are the most indelible party in a film. It is a fact that people and not technology make film as a form to express the society we live in. A unique act of art acting cannot just be faked. An actor cannot give anything out if the actor has nothing inside. In this paper, we will examine the concept of acting and the role it plays in film. We will then examine it within the context of method acting in Lancelot Oduwa Imasuen’s Invasion 1897 (2014) in order to identify and expose the slopping acting of the white cast. No doubt, the director’s casting is representational by establishing the identity of the actors of the period of the Benin Kingdom over a hundred years ago. Taking note of the above factor, this paper strives to throw the firework on the director as the master craftsman who casts his actor and is the guiding force that make all the decisions. We will then tender hints or clues towards the best bib to harness the actors of period characters by nourishing and nurturing to give a spruce acting.